Atonal- and achaete-scute-related genes in the annelid Platynereis dumerilii: insights into the evolution of neural basic-Helix-Loop-Helix genes - Simionato, Elena; Arendt, Detlev (BMC evolutionary biology, 2008)
Functional studies in model organisms, such as vertebrates and Drosophila, have shown that basic Helix-loop-Helix (bHLH) proteins have important roles in different steps of neurogenesis, from the acquisition of neural fate to the differentiation into specific neural cell types. However, these studies highlighted many differences in the expression and function of orthologous bHLH proteins during neural development between vertebrates and Drosophila. To understand how the functions of neural bHLH genes have evolved among bilaterians, we have performed a detailed study of bHLH genes during nervous system development in the polychaete annelid, Platynereis dumerilii, an organism which is evolutionary distant from both Drosophila and vertebrates.